Analysis Study on Cultivating Critical Intercultural Language Pedagogy Through Writing Personal Cultural Narratives and Reflections - Sari, Dwi Rosita; Suwandi, Edi (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
In todays interconnected world, intercultural competence is essential for effective communication across diverse cultural contexts. Traditional language education often emphasizes linguistic accuracy and cultural superficialities, neglecting deeper intercultural understanding. Critical Intercultural Language Pedagogy (CILP) offers an innovative framework that integrates cultural reflection, critical analysis, and writing practices to foster intercultural awareness and critical consciousness among learners. This study investigates the impact of writing-based interventions, specifically 'Individual Cultural Journeys,' within the CILP framework on students intercultural competence. Employing a pre-experimental design with a one-group pre-test and post-test methodology, 32 English majors participated in reflective writing activities before and after targeted intercultural interventions. Data were collected through pre- and post-intervention assessments of writing quality using a structured rubric and analyzed statistically via paired-sample t-tests. The results indicated significant improvements in students' intercultural awareness and writing abilities, evidenced by a substantial increase in post-test scores (p < 0.001) and large effect sizes. These findings underscore the efficacy of integrating reflective, culturally oriented writing tasks within language instruction to enhance intercultural competence. The study concludes that adopting critical, reflective pedagogies rooted in CILP can transform language education into a powerful tool for developing socially conscious and culturally competent global citizens, equipping learners to navigate and negotiate cultural differences effectively in an increasingly interconnected world.